2006
DOI: 10.1007/s10535-005-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Water transport in maize roots under the influence of mercuric chloride and water stress: a role of water channels

Abstract: The influence of inhibitor of water channels, HgCl 2 , on water diffusion in maize (Zea mays L.) seedling roots was investigated with the pulsed nuclear magnetic resonance (NMR) method. Blocking of water channels decreased the water permeability of cell membranes by 1.5 -2 times. This effect of HgCl 2 was exhibited only in the roots of seedlings grown in a nutrient solution containing Ca 2+ and was reversed with Hg-scavenging agent β-mercaptoethanol. Subsequent incubation of Ca 2+ -deficient roots in the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
1
15
0
2
Order By: Relevance
“…The diffusion time, t d , was chosen to be 300 ms taking into account the following reasons: 1) to exclude the relaxational contribution to the diffusion decay of the apoplastic water, which is characterized by short spin-lattice relaxation times (T 1 < 100 ms) and 2) to reveal the region of hindered diffusion where the contribution of membrane permeability is significant. Moreover, previously it was shown (Ionenko et al 2006, Ionenko andAnisimov 2007) that the inhibition of the diffusion by mercuric chloride was more pronounced at t d > 100 ms.…”
Section: Nmr Measurement Of Water Diffusion Coefficientsmentioning
confidence: 87%
See 2 more Smart Citations
“…The diffusion time, t d , was chosen to be 300 ms taking into account the following reasons: 1) to exclude the relaxational contribution to the diffusion decay of the apoplastic water, which is characterized by short spin-lattice relaxation times (T 1 < 100 ms) and 2) to reveal the region of hindered diffusion where the contribution of membrane permeability is significant. Moreover, previously it was shown (Ionenko et al 2006, Ionenko andAnisimov 2007) that the inhibition of the diffusion by mercuric chloride was more pronounced at t d > 100 ms.…”
Section: Nmr Measurement Of Water Diffusion Coefficientsmentioning
confidence: 87%
“…Inhibitor concentration and the time of incubation were chosen according to Maggio and Joly (1995), Tazawa et al (1997), Zhang and Tyerman (1999) and Ionenko and Anisimov (2007). It was shown that 0.1 mM HgCl 2 does not induce considerable side effects (Ionenko et al 2006), is not toxic (Willmer et al 1999), and does not damage membranes significantly (Wan and Zwiazek 1999).…”
Section: Plant Growth Conditions and Preparation Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium is also a crucial intracellular messenger (Marschner 1995;White and Broadley 2003). In a recent report, it has been demonstrated that the inhibitory effects of HgCl 2 (a common aquaporin blocker but also a general metabolism inhibitor) on root water transport in maize, were only seen provided that the plant nutrient solution contained Ca 2+ (Ionenko et al 2006). These data were interpreted to mean that Ca 2+ plays an important role in the up-regulation of water channel activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the previous studies have focused on individual roles of Ca 2+ on water transport regulation, either at the membrane Alleva et al 2006) or at the cell or root level Ionenko et al 2006), the aim of this paper was to investigate how Ca 2+ can have multiple, and possibly opposite effects in influencing the function of aquaporins. This question was addressed in pepper (Capsicum annuum L.) plants grown in control and salinity conditions.…”
Section: Introductionmentioning
confidence: 99%